2007
DOI: 10.1089/ten.2006.0408
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Engineering of Skeletal Muscle

Abstract: Loss of skeletal muscle profoundly affects the health and well-being of patients, and there currently is no way to replace lost muscle. We believe that a key step in the development of a prosthesis for reconstruction of dysfunctional muscular tissue is the ability to reconstitute the in vivo-like 3-dimensional (3D) organization of skeletal muscle in vitro with isolated satellite cells. In our present proof of principle studies, we have successfully constructed a multilayered culture of skeletal muscle cells, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 24 publications
2
47
0
Order By: Relevance
“…This has represented a major limitation in previous studies (2,23), and growth factors have been suggested to improve nerve regeneration (24) and new capillary formation (25,26). In our experimental model, treated muscles showed the presence of neuromuscular junctions on both GFP ϩ and GFP Ϫ myofibers, as demonstrated through labeling with fluorescent ␣-bungarotoxin (Fig.…”
Section: Functional Reconstruction Of Implanted Musclesmentioning
confidence: 72%
See 1 more Smart Citation
“…This has represented a major limitation in previous studies (2,23), and growth factors have been suggested to improve nerve regeneration (24) and new capillary formation (25,26). In our experimental model, treated muscles showed the presence of neuromuscular junctions on both GFP ϩ and GFP Ϫ myofibers, as demonstrated through labeling with fluorescent ␣-bungarotoxin (Fig.…”
Section: Functional Reconstruction Of Implanted Musclesmentioning
confidence: 72%
“…In vitro approaches based on fabrication of functional muscle before in vivo transplantation showed several limitations (2), due to the intrinsic complexity of large-organ reconstruction. Besides, it is well established that in mammals, skeletal muscle can repair its damaged areas only in the presence of a supporting scaffold (3).…”
mentioning
confidence: 99%
“…We envisioned a composite fiber that could be utilized as a temporary substrate to stimulate tissue formation controlled by electrochemical signals as well as continuous mechanical stimulation under normal regeneration processes, i.e. muscular or neural tissue [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Along with the structural maturation, these constructs were able to generate contractile force after two to four weeks in culture. Remarkably, these biomimetic muscles elicited contractile-force amplitudes of about 10-100 fold higher than previously described in vitro engineered muscles [43,162,164,165]. The in vivo behaviour of the engineered muscles was monitored using a mouse dorsal window implantation model.…”
Section: Transplantation Of In Vitro Fabricated Muscle Tissuesmentioning
confidence: 86%